The Role of Dynamics in Face sheet/Core Interface Debonding of Sandwich Panels - Burlayenko, Vyacheslav N.; Dimitrova, Svetlana D. (University of Lyon, 2022)
The current research addresses the study of debonding the face sheet from the core in a sandwich structure in dynamic regime by means of the use of a cohesive zone model accounting for contact and friction nonlinear effects. The finite element method within the ABAQUS environment is used for modeling and simulations of the dynamic debonding propagation problem. By numerical examples, the influence of different parameters, such as the adhesive properties in terms of the interface strength and toughness and the type of traction separation law and types and rates of the imposed loading, in relation to the double cantilever beam test are estimated. The obtained results demonstrate the relevance of both the adhesive properties and loading conditions, the changes of which may notably modify the stress state near the interface crack tip and the debonding evolution in the sandwich specimen in dynamics.
Keywords: face sheet; dynamic regime; sandwich structure; adhesive properties; voltage